Reconstructing the Integrated Galuh Cultural Value System: Cultural Memory, Social Cohesion, Ethical Governance, and Historical Consciousness in the Gandoang Manuscript - Azka Irham Maulana; Sudarto Sudarto; Dadan Ramdani (Universitas Galuh, 2026)
Historical manuscripts constitute primary sources that document historical dynamics, systems of knowledge, and cultural values within a society. Scholarship on the Gandoang Manuscript has largely emphasized philological aspects, whereas the local wisdom that shapes Galuh identity has received limited attention. This study aims to examine the representation of silih asah, silih asih, and silih asuh in the Gandoang Manuscript as foundational elements of Galuh local wisdom. The research employed a qualitative approach using content analysis of the manuscript in its transliterated and translated forms, complemented by a literature review on Galuh history, Sundanese manuscripts, and the concept of local wisdom. The analysis proceeded through thematic identification, data categorization, contextual interpretation, and theoretical synthesis. The findings indicate that the Gandoang Manuscript articulates three principal dimensions of local wisdom: knowledge transmission (silih asah), social solidarity (silih asih), and ethical leadership (silih asuh). These values constitute a cultural system that sustains collective memory and reinforces Galuh identity. The study extends current understanding of manuscripts as media for cultural value transmission and provides a conceptual basis for history education grounded in local heritage and for the preservation of Sundanese manuscript traditions.